[CrF(O2CtBu)2]9: Synthesis and Characterization of a Regular Homometallic Ring with an Odd Number of Metal Centers and Electrons. (13th June 2016) - Woolfson, Robert J.; Timco, Grigore A.; Chiesa, Alessandro; Vitorica‐Yrezabal, Inigo J.; Tuna, Floriana; Guidi, Tatiana; Pavarini, Eva; Santini, Paolo; Carretta, Stefano; Winpenny, Richard E. P.
Abstract: The first regular homometallic ring containing an odd number of metal centers is reported. The ring was synthesized by means of amine‐templated self‐assembly. Extensive physical characterization studies, including magnetic measurements, powder inelastic neutron scattering (INS), and DFT calculations, show that the molecule has a near perfect match to the expected behavior for a frustrated system with the lowest energy pair of S =1/2 spin states separated by only 0.1 meV (0.8 cm −1 ).